Identifying gene targets for brain-related traits using transcriptomic and methylomic data from blood - Qi T; Wu Y; Zeng J; Zhang FT; Xue AL; Jiang LD; Zhu ZH; Kemper K; Yengo L; Zheng ZL; eQTLGen Consortium; Marioni RE; et al. (NATURE PUBLISHING GROUP, 2022)
Understanding the difference in genetic regulation of gene expression between brain and blood is important for discovering genes for brain-related traits and disorders. Here, we estimate the correlation of genetic effects at the top-associated cis-expression or -DNA methylation (DNAm) quantitative trait loci (cis-eQTLs or cis-mQTLs) between brain and blood (r(b)). Using publicly available data, we find that genetic effects at the top cis-eQTLs or mQTLs are highly correlated between independent brain and blood samples ((r) over cap (b) = 0.70 for ciseQTLs and (r) over cap (b) = 0.78 for cis-mQTLs). Using meta-analyzed brain cis-eQTL/mQTL data (n = 526 to 1194), we identify 61 genes and 167 DNAm sites associated with four brain-related phenotypes, most of which are a subset of the discoveries (97 genes and 295 DNAm sites) using data from blood with larger sample sizes (n = 1980 to 14,115). Our results demonstrate the gain of power in gene discovery for brain-related phenotypes using blood cis-eQTL/mQTL data with large sample sizes.